2018
DOI: 10.1016/j.jacc.2018.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trajectories of Left Ventricular Ejection Fraction in Heart Failure

Abstract: LVEF trajectories vary in HF depending on a number of disease modifiers, but an inverted U-shaped pattern with lower LVEF at both ends of the distribution emerged. A declining LVEF in the preceding period was associated with higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
157
3
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(184 citation statements)
references
References 18 publications
20
157
3
4
Order By: Relevance
“…This finding is consistent with previous AHF registry data, with evidence that reduced LVEF is a powerful predictor of CV outcomes in post‐myocardial infarction patients and with recent evidence that the association between ischaemic status and new ischaemic or HF events was greater in patients with lower LVEF . The stronger association between LVEF and risk of future CV events in patients with ischaemic heart disease vs. those with non‐ischaemic aetiologies might be related to disease in other organs that ultimately influenced outcomes or to a lower likelihood of improvement of LVEF over time as some patients with an ischaemic aetiology experience less remodelling compared to those with a non‐ischaemic aetiology of HF …”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous AHF registry data, with evidence that reduced LVEF is a powerful predictor of CV outcomes in post‐myocardial infarction patients and with recent evidence that the association between ischaemic status and new ischaemic or HF events was greater in patients with lower LVEF . The stronger association between LVEF and risk of future CV events in patients with ischaemic heart disease vs. those with non‐ischaemic aetiologies might be related to disease in other organs that ultimately influenced outcomes or to a lower likelihood of improvement of LVEF over time as some patients with an ischaemic aetiology experience less remodelling compared to those with a non‐ischaemic aetiology of HF …”
Section: Discussionsupporting
confidence: 91%
“…Multiple seminal heart failure studies have reported that low baseline LVEF is significantly associated with a greater increase in LVEF over time. [21][22][23][24][25] Several prior published studies in cardio-oncology support our observations. In the Multidisciplinary Approach to Novel Therapies in Cardio-Oncology Research (MANTICORE 101-Breast) trial, for example, a negative relationship was observed between baseline LVEF and change in LVEF.…”
Section: Discussionsupporting
confidence: 88%
“…Patients were referred to the HF clinic mostly by the cardiology or internal medicine departments, and to a lesser extent by the emergency or other hospital departments. The criteria for referral to the HF clinic were HF with at least one hospitalization and/or depressed systolic function . All patients were seen regularly for follow‐up visits at the HF clinic according to their clinical needs and treated according to a unified protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The criteria for referral to the HF clinic were HF with at least one hospitalization and/or depressed systolic function. 9,10 All patients were seen regularly for follow-up visits at the HF clinic according to their clinical needs and treated according to a unified protocol. Follow-up visits included a minimum of one visit with a nurse every 3 months and one visit with a physician (cardiologist, internist, or family physician) every 6 months, as well as optional visits with specialists in geriatrics, psychiatry, and rehabilitation.…”
Section: Study Population and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation